Psychrobacter sp: perchlorate reducing bacteria, isolated from marine sediments from Margarita Bay, Antarctica. (LACCEI, 2024)
Perchlorate (ClO4-) is an ion that occurs naturally in Antarctica, it is considered an emerging pollutant because it is a powerful endocrine disruptor that affects the functioning of the thyroid gland and the growth and development of humans and biota. The objective of this study was to characterize salt-tolerant bacteria that reduce (ClO4-) from marine sediments of Bahía Margarita, Antarctica, collected in the V Colombian Scientific Expedition to Antarctica "Almirante Tono" in 2019. The methodology used included three stages: [1] Isolation of the bacteria: for which broth and LB agar modified with seawater were used [2] Morphological and biochemical characterization of the isolated strains: through Gram staining, tests for catalase, oxidase and BBL Crystal [3] Susceptibility tests (NaCl and ClO4-) and ClO4- reduction test using selective electrode. The bacterial isolates grew at 10 °C for 7 days, tolerated NaCl concentrations up to 20% v/v and (ClO4-) concentrations up to 10,000 mg/L with pH variations between 6.5 to 12.0. This contaminant was reduced by the isolated strains in percentages between 18% and 41%. The morphological and biochemical characterization of the isolated strains indicated that they were related to the genus Psychrobacter. In conclusion, salt-tolerant bacteria isolated from marine sediments in Margarita Bay, Antarctica are promising resources for bioremediation of (ClO4-) pollution in ecosystems.